2020
DOI: 10.1038/s41419-020-03047-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC9 promotes gefitinib resistance in NSCLC by epigenetic repression of DUSP1

Abstract: Resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), such as gefitinib, has greatly affected clinical outcomes in non-small cell lung cancer (NSCLC) patients. The long noncoding RNAs (lncRNAs) are known to regulate tumorigenesis and cancer progression, but their contributions to NSCLC gefitinib resistance remain poorly understood. In this study, by analyzing the differentially expressed lncRNAs in gefitinib-resistant cells and gefitinib-sensitive cells in the National Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…Multiple cancer-related lncRNAs have been identified, such as MALAT1, HOTAIR, lncRNA-ATB, FAL1, EPIC1, LINK-A, and PXN-AS1 ( Gutschner et al, 2013 ; Hu et al, 2014 ; Yuan et al, 2014 ; Lin et al, 2016 ; Yuan et al, 2017 ; Wang et al, 2018 ; Li H. et al, 2020 ). In lung cancer, lncRNAs PIK3CD-AS2, HCP5, SNHG15, SNHG11, CASC9, and ALAL-1 have oncogenic roles ( Athie et al, 2020 ; Cheng et al, 2020 ; Chen Z. et al, 2020 ; Huang et al, 2020 ; Li C. et al, 2020 ; Zheng et al, 2020 ). In contrast, lncRNAs NORAD, BRCAT54, CASC7, and HSPC324 have tumor-suppressive roles ( Tan et al, 2019 ; Chen L. et al, 2020 ; Jafarzadeh et al, 2020 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cancer-related lncRNAs have been identified, such as MALAT1, HOTAIR, lncRNA-ATB, FAL1, EPIC1, LINK-A, and PXN-AS1 ( Gutschner et al, 2013 ; Hu et al, 2014 ; Yuan et al, 2014 ; Lin et al, 2016 ; Yuan et al, 2017 ; Wang et al, 2018 ; Li H. et al, 2020 ). In lung cancer, lncRNAs PIK3CD-AS2, HCP5, SNHG15, SNHG11, CASC9, and ALAL-1 have oncogenic roles ( Athie et al, 2020 ; Cheng et al, 2020 ; Chen Z. et al, 2020 ; Huang et al, 2020 ; Li C. et al, 2020 ; Zheng et al, 2020 ). In contrast, lncRNAs NORAD, BRCAT54, CASC7, and HSPC324 have tumor-suppressive roles ( Tan et al, 2019 ; Chen L. et al, 2020 ; Jafarzadeh et al, 2020 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it was urgent for us to improve the prognosis of NSCLC patients by finding novel and improved therapies. More and more evidences have showed that a large number of lncRNAs played extremely pivotal biological roles in the progression of NSCLC (20). For example, LncRNA KTN1-AS1, CASC9, ABHD11-AS1, LINC00467 could participate in the progress of NSCLC (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Top‐ranked genes in this signature are known downstream targets of EZH2 and play a proven role in tumorigenesis (Supplementary Table S8). For example, EZH2 binds to the DUSP1 promoter inducing H3K27 trimethylation, which subsequently suppresses DUSP1 expression 48 . EZH2 also directly regulates the key tumour suppressor, miRNA101, in a negative feedback loop 49 and decreasing levels of miRNA101 are associated with multiple tumours, including colon, liver, lung, ovarian and prostate 50 .…”
Section: Discussionmentioning
confidence: 99%